2020
DOI: 10.1017/jpa.2019.88
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT study of Middle Ordovician Spumellaria (radiolarians) from western Newfoundland, Canada

Abstract: A new, previously undescribed Middle Ordovician (middle Darriwilian: Dw2) radiolarian assemblage has been recovered from the Table Cove Formation at Piccadilly Quarry, western Newfoundland. Constituents of the fauna described herein are both distinctive and exceptionally well preserved. Three-dimensional X-ray micro-computed tomography (μ-CT) is used to make a detailed examination of four key spumellarian specimens. This technology enables visualization of hitherto ambiguous details of the internal morphologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…One specimen with an uncertain taxonomic affiliation, here described as Haplotaeniatum albaensis, was examined using the Zeiss Xradia Versa XRM-500 high-resolution scanner at the Julius Kruttschnitt Mineral Research Centre, The University of Queensland, following the method developed by Kachovich et al (2019). Prior to scanning, machine parameters and configuration requirements were set according to the standard set-up developed by Kinney & Nichols (1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One specimen with an uncertain taxonomic affiliation, here described as Haplotaeniatum albaensis, was examined using the Zeiss Xradia Versa XRM-500 high-resolution scanner at the Julius Kruttschnitt Mineral Research Centre, The University of Queensland, following the method developed by Kachovich et al (2019). Prior to scanning, machine parameters and configuration requirements were set according to the standard set-up developed by Kinney & Nichols (1992).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have questioned the validity of the number of spheres and spines as a diagnostic feature, and some researchers claim that the presence or absence of these features relate to ontogeny (Noble & Aitchison, 1995;Danelian & Popov, 2003;Suzuki, 2006;Maletz, 2011; S Kachovich, unpub. PhD thesis, The University of Queensland, 2018; Kachovich & Aitchison, 2020). This is evident from the variations in the shell dimensions and numbers of spines reported in many of the studies that have reported inaniguttids (Nazarov & Popov, 1980;Nazarov & Ormiston, 1984, 1993Nazarov, 1988;Wang, 1993;Li, 1995; Danelian & Clarkson, 1998;Danelian, 1999;Danelian & Floyd, 2001;Noble & Webby, 2009;Pouille et al 2013).…”
mentioning
confidence: 99%
“…Co-occurring conodonts allow correlation to the late Dw2 Histiodella kristinae subzone (Stouge, 1984).
Figure 1.Locality map showing position of study area (after Cooper et al, 2001; Kachovich and Aitchison, 2020). Inset map shows Port au Port Peninsula's location in relation to the rest of Newfoundland.
…”
Section: Geologic Settingmentioning
confidence: 99%
“…In order to fully document a well-preserved radiolarian fauna from the middle Darriwilian Table Cove Formation in Newfoundland, this paper is intended to complement earlier work of Kachovich and Aitchison (2020) that described spumellarian radiolarians from the same location. Archaeospicularid and entactiniid radiolarians, together with forms that remain in open nomenclature, are described herein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation